Literasi Kesehatan Mental: Dampak Perilaku dan Resiliensi Sosial Pada Remaja - Septiana, Nila Zaimatus; Istiqomah, Nanda; Rahayu, Dwi Sri (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
The high prevalence of mental health disorders results in a social and economic burden, yet only 10% receive professional treatment. This is due to low mental health literacy, which affects how they get help and the formation of group resilience. This research has two questions: how is students mental health literacy during and after the pandemic? And what impact does the lack of literacy have on students’ behaviour and social resilience? This research uses a qualitative approach with a case study type. Data collection was carried out by focus group discussions with five subjects who experienced mental health disorders, according to the initial study. Data analysis in this study used narrative analysis and data validation using data source triangulation. The results showed that low mental health literacy leads to anxiety, stress, withdrawal, difficulty opening, destructive behaviour, and self-harm. Impacts on social resilience include negative stigma and lack of social support. The research concluded that low literacy negatively impacts behaviour and professional help.